2021
DOI: 10.1002/ca.23781
|View full text |Cite
|
Sign up to set email alerts
|

Motivation and learning methods of anatomy: Associations with mental well‐being

Abstract: Appropriate anatomy education for speech and language therapists is a crucial part of preparation for clinical practice. While much research has been conducted regarding the anatomical education of medical students, there is a paucity of evidence for speech and language therapy students. This study assessed the methods employed by a cohort of first-year speech and language therapy students to learn anatomy, their perceptions of the clinical importance of anatomy and motivation to learn anatomy (using a modifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 62 publications
0
6
1
Order By: Relevance
“…This finding is similar to a recent study, 31 where 87% of healthcare professional trainees (chiropractic, dental, medical) were interested in anatomy program content. This may partly because they consider anatomy knowledge as essential for clinical programs, as previously been reported in another study on speech and language therapy students 32 …”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This finding is similar to a recent study, 31 where 87% of healthcare professional trainees (chiropractic, dental, medical) were interested in anatomy program content. This may partly because they consider anatomy knowledge as essential for clinical programs, as previously been reported in another study on speech and language therapy students 32 …”
Section: Discussioncontrasting
confidence: 73%
“…This may partly because they consider anatomy knowledge as essential for clinical programs, as previously been reported in another study on speech and language therapy students. 32 Consistent with the motivations to study anatomy summarized above, many alumni are currently in clinical professions, some are still students, and others are in research or managerial positions, with only a minority in academic positions. Data from the University of Toronto 17 showed that 26% of their PhD graduates are in an academic position, compared with only 9.4% of the PhD graduate responses in this study.…”
Section: Why Study Anatomy?mentioning
confidence: 81%
“…These components of the motivational profile, ascertained by the SMQII, share similarities to those of health professional students. 3,26,27 However, in addition, science students reported high levels of self-determination and self-efficacy, potentially setting them apart from other cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…The present scenario leaves very little space for incorporating evolved education methods and emphasizing clinical details, core focus areas in contemporary medical education. The reported knock‐on effect is a lower level of motivation/interest among students exposed to non‐research‐based anatomy knowledge (Fives et al, 2022). This seems consistent with the association between evolved teaching/learning methods and high levels of student motivation (Paech et al, 2017).…”
Section: Discussionmentioning
confidence: 99%